NON-SPECIFIC PROTECTION FACTORS AND INFLAMMATORY MEDIATORS IN URINE OF CHILDREN WITH GLOMERULONEPHRITIS IN THE PRESENCE OF HERPESVIRAL INFECTION. NOTICE I. DETERMINATION OF SIGA AND MCP-1 - I. Bagdasarova; I. Kruglikova; E. Kornilina; V. Kruglikov (Ukrainian Journal of Nephrology and Dialysis, 2016)
The aim of this work was the study of indicators characterizing the local immunity in patients with various forms of glomerulonephritis by presence of herpesviral infection.Materials and methods. A quantitative estimation of the content of sIgA and MCP-1 in urine of 47patients with glomerulonephritis and 10 apparently healthy individuals was conducted.Results. The decrease of sIgA level and reliable increase ofMCP-1 level were observed in urine of patients with glomerulonephritis. There was a significant increase in the level of these indices in hormone-resistant patients with nephrotic form of glomerulonephritis; in patients with severe course of the disease and also in the absence of remission. More such changes were found in children with active (reactivated) herpesviral infections.Conclusion. There has been confirmed the importance of the study of immunologic parameters in the urine of patients with glomerulonephritis to characterize immunopathological process in the kidney and prognosis of the disease.